2018
DOI: 10.1139/cjfas-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving release efficiency of cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) in the Barents Sea demersal trawl fishery by stimulating escape behaviour

Abstract: Abstract:We tested the ability of stimulators to improve the release efficiency of cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) through the meshes of a square mesh section installed in a trawl. The section was tested in three different configurations: without any stimulation device, with a mechanical stimulation device, and with LED light stimulation devices. We analysed and compared the behaviour of cod and haddock in all three configurations based on release results and underwater recordings. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…This downward swimming behavior of cod is well documented in earlier studies (e.g. Engås and Godø, 1989;Wardle, 1993;Grimaldo et al, 2017) and was observed for 80.3 % (95% CI: 70.4-88.7 %) of the 71 cod observed entering the section. Compared with cod, redfish entered the section relatively evenly distributed, a behavior also documented in the literature (e.g.…”
Section: Underwater Recordingssupporting
confidence: 85%
See 1 more Smart Citation
“…This downward swimming behavior of cod is well documented in earlier studies (e.g. Engås and Godø, 1989;Wardle, 1993;Grimaldo et al, 2017) and was observed for 80.3 % (95% CI: 70.4-88.7 %) of the 71 cod observed entering the section. Compared with cod, redfish entered the section relatively evenly distributed, a behavior also documented in the literature (e.g.…”
Section: Underwater Recordingssupporting
confidence: 85%
“…This high contact value is in line with results for the double steel grid system presented by Larsen et al (2016), which showed that redfish were effective at contacting the upper grid of the section tested. This indicates, that compared with cod, which have been reported multiple times to seek outlets in a mainly downwards direction (Engås and Godø, 1989;Wardle, 1993;Grimaldo et al, 2017), redfish…”
Section: Discussionmentioning
confidence: 83%
“…When white LED lights were installed on the SMP or in the panel right below the SMP, the release efficiency through the SMP was not significantly improved for either hake or blue whiting. Grimaldo et al (2017) tested whether green LED lights could improve the release efficiency of cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) through a square mesh section. No significant differences were found for cod, whereas the results for haddock only indicated an effect for the smaller individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulators are designed to trigger fish escape behaviour, but the results obtained so far have shown varying degrees of success (e.g. Glass and Wardle 1995, Herrmann et al 2014, Grimaldo et al 2017). Mechanical stimulators have been shown to reduce the retention rate of some juvenile fish species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The poor contact probability is likely due to the excessive distance of the panel from the codline ), a part of the net where fish have no reason to change direction and swim up through the panel meshes. This could be changed by placing stimulation devices in the vicinity of the square-mesh panel to alter swimming patterns, forcing fish to interact with the panel meshes (Brewer et al 1998;Eayrs 2007;Glass et al 1995;Herrmann et al 2015;Krag et al 2016;Grimaldo et al 2017). In this study a square-mesh panel inserted in front of the trawl failed to improve size and species selection; as a result, the present findings are to all effects negative.…”
Section: Discussionmentioning
confidence: 56%